2001
DOI: 10.1103/physreve.64.046130
|View full text |Cite
|
Sign up to set email alerts
|

Crossover phenomena in spin models with medium-range interactions and self-avoiding walks with medium-range jumps

Abstract: We study crossover phenomena in a model of self-avoiding walks with medium-range jumps, which corresponds to the limit N-->0 of an N-vector spin system with medium-range interactions. In particular, we consider the critical crossover limit that interpolates between the Gaussian and the Wilson-Fisher fixed point. The corresponding crossover functions are computed by using field-theoretical methods and an appropriate mean-field expansion. The critical crossover limit is accurately studied by numerical Monte Carl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 111 publications
(225 reference statements)
3
17
0
Order By: Relevance
“…Interestingly, this result has been recovered in Ref. [11], where in addition it was found that the constant c 1 has a universal value −2/π ≈ −0.6366. Indeed, this agrees with the value −0.624 (7) obtained from an analysis of the available data for 25 < ∼ R 2 < ∼ 70.…”
Section: Summary Of Renormalization-group Predictionssupporting
confidence: 54%
“…Interestingly, this result has been recovered in Ref. [11], where in addition it was found that the constant c 1 has a universal value −2/π ≈ −0.6366. Indeed, this agrees with the value −0.624 (7) obtained from an analysis of the available data for 25 < ∼ R 2 < ∼ 70.…”
Section: Summary Of Renormalization-group Predictionssupporting
confidence: 54%
“…13 A second use of the TPM expressions is in the description of the crossover to the θ point. As we have explained in the introduction, the crossover functions defined in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as discussed in Ref. 13 , the TPM describes the approach to the scaling limit when V m /l 3 ≪ 1, where l is the persistence length and V m is the volume occupied by a polymer blob of length l. In this paper we wish to compute the crossover functions for several quantities whose behavior in the good-solvent regime has been considered in Refs. 14, 15 . We compute numerically the TPM predictions for the second, third, and fourth virial coefficient, for the swelling factors, and the density corrections to the radius of gyration, the end-to-end distance, and the hydrodynamic radius.…”
Section: Introductionmentioning
confidence: 99%
“…One can use field theory and compute the crossover functions by resumming the perturbative series [10,11,12,13]. Alternatively, one can use the fact that the field-theoretical crossover is equivalent to the critical crossover that occurs in models with medium-range interactions [14,15,13,16,17]. This allows one to use the wealth of results available for these spin systems [14,18,19,15,13,17].…”
Section: Introductionmentioning
confidence: 99%